A novel assessment technique does not produce more reliable estimates of maximal neuromuscular strength - Buskard, A. N. L.; Roberson, K. B.; Signorile, J. F. (Research Quarterly for Exercise and Sport, 2021)
Accurate determinations of individuals` one-repetition maximum (1RM) are critical when evaluating the effectiveness of an exercise intervention involving progressive resistance training (RT). Traditional ("bottom-up"; BT) testing methods involve progressions from low to maximal loads and are commonly used in clinical and laboratory environments. Concerns about the reliability of BT testing in certain populations suggest a different technique may be more effective.